Direct Noncatalytic Electrophilic Trifluoroacetylation of Electron-Rich Pyrazoles - Yarmoliuk, Dmytro V.; Arkhipov, Viatcheslav V.; Stambirskyi, Maksym V.; Dmytriv, Yurii V.; Shishkin, Oleg V.; Tolmachev, Andrei A.; Mykhailiuk, Pavel K. (Synthesis, 2014)
Electron-rich N-substituted pyrazoles smoothly reacted with trifluoroacetic anhydride in pyridine to form the corresponding trifluoromethyl ketones in good yields.
Keywords: trifluoromethyl group; trifluoroacetyl group; fluorine; pyrazole; building blocks